Determinants of transfer pricing audit selection among multinational enterprises (MNES) in Malaysia - Baharuddin, Juliana (2020)
International cross border transfer pricing is a subject that no multinational enterprises, regardless of size and location, can afford to ignore. In today’s economy where multinational enterprises play an increasingly prominent role, transfer pricing continues to be high on the agenda of tax administrations and taxpayer alike. Previous studies have shown that the selection of transfer pricing cases for audit in Malaysia was influenced by certain characteristics of the multinational enterprises. The objective of this study is to find out statistical evidence whether firm size, profitability margin, types of industry as well as tax incentives were still the influencing factors in the selection of transfer pricing audit. The findings from this study prove that the factors that were previously considered important are no more the main determinants of a case being selected. Economic circumstances which lead for a business restructuring or changes in characterization of entity might be considered in determining the audit cases. This study will help the tax authorities to identify the current audit case selection method. For taxpayers and tax practitioners, the findings from this research study will help them to identify risks and possible red-flags to be chosen for audit. In this way, taxpayers can be more prepared and better adhere to the prevailing pricing policy method at a consistent rate in line with domestic and international guidelines.